A Reversed-Phase Mode LC-MS/MS Method Using a Polysaccharide Chiral Selector for Simultaneous Quantitation of Each Enantiomer of Tramadol and its Metabolites in Human Plasma and Evaluation of CYP-Mediated Stereoselective Demethylation. Issue 3 (June 2020) - Suzuki, Koji; Naito, Takafumi; Tanaka, Hironari; Yamada, Yasuhide; Itoh, Kunihiko; Kawakami, Junichi
Abstract : Background: The enantiomeric pharmacokinetics and metabolism of tramadol and its metabolites have not fully been understood. This study aimed to develop a reversed-phase mode liquid chromatography coupled to a tandem mass spectrometry method for the enantiomeric quantitation of tramadol and its metabolites in human plasma and to evaluate the stereoselective demethylation. Methods: Racemic tramadol and its metabolites in plasma specimens were separated using a chiral selector coated with cellulose tris(3, 5-dimethylphenylcarbamate) on silica gel under a reversed-phase mode. The mass spectrometer ran in the positive ion multiple-reaction monitoring mode. This method was performed to quantify plasma samples from 20 cancer patients treated with oral tramadol. The stereoselective demethylation was evaluated using recombinant cytochrome P450 (CYP) enzymes. Results: The calibration curves of (+)- and (−)-tramadol, (+)- and (−)- O -desmethyltramadol (ODT), and (+)- and (−)- N -desmethyltramadol (NDT) were linear over the plasma concentration ranges of 6.25–800, 1.25–160, and 3.13–400 ng/mL for the respective enantiomers. In the present method, the intra- and inter-day accuracies and imprecisions were 94.2%–108.3% and 0.5%–6.0% for all analytes. The plasma concentrations of (+)-tramadol and NDT were higher than those of (−)-enantiomers. In contrast, no differences were observed between the plasma concentrations of (+)- and (−)-ODT. In the demethylation assay, the O -demethylations of tramadol and NDT by CYP2D6 were (−)-form-selective. Conclusions: The present method can be useful in the enantiomeric evaluation of tramadol and its metabolites in human plasma. Although CYP2D6 contributed to the stereoselective demethylation of tramadol, remarkable differences between (+)- and (−)-ODT were not observed in the plasma of the cancer patients. Abstract : Supplemental Digital Content is Available in the Text.